Analysis of Air Traffic Density using GIS, Case Study: Jakarta-Surabaya - Sekartadji, Ratih; Ahyudanari, Ervina; Jaelani, Lalu Muhamad (Institut Teknologi Sepuluh Nopember, 2017)
The growth of air transportation is encouraged by high demand to travel fast. Jakarta-Surabaya route is placed as the fourth busiest traffic in the world. This busy route still possible to increase, unless there is an alternative mode of transport to serve the demand of this route. Aircraft flies at a certain flight level that is influenced by the flight distance and the type of aircraft. Jakarta-Surabaya route is served by aircrafts with different types. This means that some flight levels between Jakarta and Surabaya are occupied by these serving aircrafts. On the other hand, at the same flight level, there will be some other planes for other routes. This research attempts to picture the density of the flight level of Jakarta-Surabaya route. The density value will be useful to predict the air quality and the available air space to add the flight frequencies. Data collection of Jakarta-Surabaya flights was aimed to identify the occupied flight level by this route. For other routes that may be crossed or in line with the Jakarta-Surabaya route, are derived from International Civil Aviation (ICAO) Charts. Incorporating the route volume resulting the traffic derivation from the charts and scheduled flight into the network attribute of GIS. Data histories of the flight density from ICAO Charts are used to predict the future density utilizing the GIS. The horizon year for this research is year 2030 where some airports will be improved into higher level airport groups, according to PM No. 69 year 2013.